Answer:
(-6,-4)
Explanation:
I'm going to solve this system by elimination. You can only do this when both equations have the same form; here it is ax+by=c. What that means is a variable gets eliminated after adding or subtracting the equations.
This elimination can be applied to this system by adding the equations. This will elimination the y part because they are opposites.
x+y=-10
2x-y=-8
-‐---------- Adding.
3x+0=-18
3x=-18
Divide both sides by 3:
x=-18/3
x=-6
Using one of the equations we started with along with x=-6, we can find y.
x+y=-10 with x=-6
-6+y=-10
Add 6 on both sides:
y=-4
The solution is (x,y)=(-6 -4).